Continuous Glucose Monitoring Diving and Diabetes: An Update of the Swedish Recommendations. (January 2020) - Jendle, Johan; Adolfsson, Peter
Divers travel to different countries to explore various diving sites worldwide. In 2005, the Divers Alert Network (DAN) published their guidelines for recreational diving and diabetes mellitus. However, although years have passed, there is still no consensus in the form of international guidelines on diabetes and diving. Large differences are noted with regard to the regulations in different countries. Furthermore, the diabetes technology has evolved rapidly and is not reflected in current international guidelines. This is potentially both a medical and an insurance problem for a diver with diabetes. We present a short summary of the recently updated Swedish recommendations for recreational divers with type 1 diabetes mellitus, focusing on the use of continuous glucose monitoring and continuous subcutaneous insulin infusion during such circumstances.